Promotion of Business on Social Media ("Journal "U". Economy. Management. Finance.", 2017)
The audience of social networks promptly grows in Russia that does it very perspective for business promotion. The article provides the overview of the main methods of promotion of business on social networks, demonstrates the main requirements to registration of groups and content for better interaction withpotential consumers of the company.
Keywords: social networks; promotion on social media; Social Media Marketing